Pengaruh Model Pembelajaran Kooperatif Tipe Round Robin Terhadap Hasil Belajar Matematika Kelas IV SD - Cantika Dinova Ramadila; Taryzca Putri Laela Ramadhani; Hery Setiyawan (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the influence of the Round Robin cooperative learning model on Mathematics Learning Outcomes in Grade IV Elementary School. The type of research used in this study is quantitative with an experimental method (pre experimental, one group, pretest-posttest design). The subject of this study is grade IV elementary school students. The data collection techniques used are observation and tests. The results of the study show that the Round Robin type cooperative learning model can affect the Mathematics Learning Outcomes of grade IV elementary school where the model can improve students' speaking skills compared to class discussions using conventional learning models.